2014
DOI: 10.1063/1.4890113
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh stability of atomically thin metallic glasses

Abstract: We report the fabrication and study of thermal stability of atomically thin ZrCu-based metallic glass films. The ultrathin films exhibit striking dynamic properties, ultrahigh thermal stability, and unique crystallization behavior with discrete crystalline nanoparticles sizes. The mechanisms for the remarkable high stability and crystallization behaviors are attributed to the dewetting process of the ultrathin film. We demonstrated a promising avenue for understanding some fundamental issues such as glassy str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…41 Alternate explanations for the link between thermal stability and film thickness of TFMGs of other materials have also been put forth. 42 Differences between amorphous and crystalline phases are primarily described by the manner in which local structural units are connected or the short range structural difference. Although amorphous/glassy materials are usually classified as disordered, on an atomic scale, they are seen to constitute a local structural order.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…41 Alternate explanations for the link between thermal stability and film thickness of TFMGs of other materials have also been put forth. 42 Differences between amorphous and crystalline phases are primarily described by the manner in which local structural units are connected or the short range structural difference. Although amorphous/glassy materials are usually classified as disordered, on an atomic scale, they are seen to constitute a local structural order.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…It has been shown that the MGs after the occurrence of LLPT often showed better stability 28,30,52 . These studies suggested that it is easier for the amorphous structure to approach the lowest energy state after relaxation [53][54][55] . These structural differences can lead to a dramatic change in other macroscopic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Physical vapor deposition, as a classic example of gas-to-solid condensation, is widely used to synthesize metallic films with various crystalline, amorphous, and crystal−glass hybrid nanostructures and includes magnetron sputtering, 74 thermal evaporation, 75 and pulsed laser deposition. 76 To date, magnetron sputtering has been developed as the most common fabrication technology for SNDP-GC materials (Figure 3). As the sputtered atoms and atom clusters deposit on the cold substrate, the cooling rate is as high as ∼10 12 K/s.…”
Section: Supra-nano-dual-phase Glass−crystal Materialsmentioning
confidence: 99%
“…The condensation of a gas/liquid to a solid is an efficient strategy for preparing SNDP-GC materials directly without postprocessing. Physical vapor deposition, as a classic example of gas-to-solid condensation, is widely used to synthesize metallic films with various crystalline, amorphous, and crystal–glass hybrid nanostructures and includes magnetron sputtering, thermal evaporation, and pulsed laser deposition . To date, magnetron sputtering has been developed as the most common fabrication technology for SNDP-GC materials (Figure ).…”
Section: Supra-nano-dual-phase Materialsmentioning
confidence: 99%